Definitions for warning signs and signs of severe dengue according to the WHO 2009 classification: Systematic review of literature. (24th April 2018) - Morra, Mostafa Ebraheem; Altibi, Ahmed M.A.; Iqtadar, Somia; Minh, Le Huu Nhat; Elawady, Sameh Samir; Hallab, Asma; Elshafay, Abdelrahman; Omer, Omer Abedlbagi; Iraqi, Ahmed; Adhikari, Purushottam; Labib, Jonair Hussein; Elhusseiny, Khaled Mosaad; et al.
Summary: Since warning signs and signs of severe dengue are defined differently between studies, we conducted a systematic review on how researchers defined these signs. We conducted an electronic search in Scopus to identify relevant articles, using key words including dengue, "warning signs, " "severe dengue, " and "classification." A total of 491 articles were identified through this search strategy and were subsequently screened by 2 independent reviewers for definitions of any of the warning or severe signs in the 2009 WHO dengue classification. We included all original articles published in English after 2009, classifying dengue by the 2009 WHO classification or providing the additional definition or criterion of warning signs and severity (besides the information of 2009 WHO). Analysis of the extracted data from 44 articles showed wide variations among definitions and cutoff values used by physicians to classify patients diagnosed with dengue infection. The establishment of clear definitions for warning signs and severity is essential to prevent unnecessary hospitalization and harmonizing the interpretation and comparability of epidemiological studies dedicated to dengue infection.